Montelukast Inhibits Platelet Activation Induced by Plasma From COVID-19 Patients - Camera, Marina; Canzano, Paola; Brambilla, Marta; Rovati, G. Enrico (Frontiers in Pharmacology, 2022)
Leukotrienes are important proinflammatory lipid mediators derived from the arachidonic acid metabolism. In particular, cysteinyl leukotrienes, LTC4, LTD4 and LTE4, are involved in many of the principal features of asthma, while more recently they have also been implicated in cardiovascular diseases. COVID-19 is characterized by an overwhelming state of inflammation, sometimes resulting in an acute respiratory distress syndrome. Furthermore, severe COVID-19 patients present an endothelial cell damage characterized by an hyperinflammatory/procoagulant state and a widespread thrombotic disease. Leukotriene receptor antagonists, such as montelukast, have long been proven to have an efficacy in asthma, while more recently they have been suggested to have a protective role also in cardiovascular diseases. As elevated levels of LTE4 have been detected in bronchoalveolar lavage of COVID-19 patients, and montelukast, in addition to its anti-inflammatory properties, has been suggested to have a protective role in cardiovascular diseases, we decided to investigate whether this drug could also affect platelet activation characteristic of COVID-19 syndrome. In this contribution we demonstrate that montelukast inhibits platelet activation induced by plasma from COVID-19 patients by preventing the surface expression of tissue factor (TF) and P-selectin, reducing the formation of circulating monocyte- and granulocyte-platelet aggregates, and, finally, in completely inhibiting the release of TFpos circulating microvescicles. These data suggest the repurposing of montelukast as a possible auxiliary treatment for COVID-19 syndrome.